Obtención y caracterización de soportes de alcohol polivinílico y quitosano para cultivo celular (2014)
ABSTRACT: Tissue engineering seeks for the possibility of the human body to regenerate itself by the creation of an artificial environment appropriate for cells. One of the approaches has been the development of scaffolds will allow the cells to grow and proliferate. In this research PVAchitosan scaffolds were developed using gas foaming/particulate leaching technique. Mechanical compression tests, scanning electron microscopy (SEM), infrared spectroscopy (FTIR) and a preliminary cell culture with Chinese hamster ovary cell line (CHO) was performed. Cell adhesion was evaluated by Giemsa stain. PVA-chitosan scaffolds showed mechanical and structural stability and an adequate porosity and interconnectivity. Pore sizes were larger than 10μm. Finally, Giemsa results for the preliminary cell culture revealed cells adhesion within the scaffold.